IV Vitamin C in Sepsis: A Latest Systematic Review and Meta-Analysis - Chengli Wen; Yuan Li; Qinxue Hu; Hui Liu; Xinxin Xu; Muhan Lü (International Journal of Clinical Practice)
Sepsis is a high-incidence disease and demands intensive care. Finding effective treatment is the key to cure sepsis. Studies have shown a lower level of vitamin C in patients with sepsis. Therefore, vitamin C supplementation has become one of the measures to treat sepsis. However, the clinical studies of vitamin C in the treatment of sepsis have been controversial. We performed a meta-analysis to evaluate vitamin C’s efficacy and safety in the treatment of sepsis. We searched four electronic databases: PubMed, Embase, Web of Science, and the Cochrane Library, and two researchers independently screened 24 eligible RCTs published in English. Our review demonstrates that intravenous (IV) vitamin C might improve short-term mortality (RR, 0.82; 95% CI, 0.65–1.02; P=0.07; and I2 = 45%) and overall mortality (RR, 0.86; 95% CI, 0.74–1.01; P=0.06; and I2 = 51%) of patients with sepsis. Moreover, the SOFA score of patients with sepsis improved significantly after treatment with vitamin C for over 72 hours (RR, 0.26; 95% CI, 0.09–0.42; P=0.002; and I2 = 0%). The main results of our study were moderate-quality evidence. More high-quality, multicenter RCTs are needed to provide more substantial evidence on the efficacy and safety of IV vitamin C for sepsis.